Postural analysis contribution in handstand position - Scotton, C.; Grosso, G; Ferraris, L.; Caire, M.; Pizzigalli, L. (Medicina dello Sport, 2015)
AIM: The aim of this study was to investigate the center of pressure (CoP) variables, during the handstand position (VRR) and their relation with the stand position, in 22 female gymnasts (mean±SD) (15.6±5.7) years old; height (152.0±0.1) cm; weight (44.1±11.3) kg and weekly hours of training (19.4±2.6).